2017
DOI: 10.2334/josnusd.16-0874
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying δ- and μ-opioid receptor agonist-induced increases in extracellular dopamine level in the nucleus accumbens of freely moving rats

Abstract: Abstract:The nucleus accumbens is a terminal area of the mesolimbic dopaminergic system that arises in the ventral tegmental area. Opioids are thought to enhance dopaminergic activity in the nucleus accumbens by activating δ-and μ-opioid receptors in the ventral tegmental area. However, δ-and μ-opioid receptor agonists increase extracellular levels of accumbal dopamine when infused directly into the nucleus accumbens of rats. Therefore, the roles of δ-and μ-opioid receptors in regulation of accumbal dopaminerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The release of DA from the ventral tegmental area (VTA) plays an important role in the rewarding effect. It has been reported that activation of opioid peptide receptors can promote feeding by palatability (Kelley, Baldo, Pratt, & Will, 2005), and later studies have found that opioid peptide agonists can increase the level of DA in nucleus accumbens (NAc), producing feelings of pleasure and reward (Saigusa, Aono, & Waddington, 2017). The DA reward system is also regulated by hormones and nutrients.…”
mentioning
confidence: 99%
“…The release of DA from the ventral tegmental area (VTA) plays an important role in the rewarding effect. It has been reported that activation of opioid peptide receptors can promote feeding by palatability (Kelley, Baldo, Pratt, & Will, 2005), and later studies have found that opioid peptide agonists can increase the level of DA in nucleus accumbens (NAc), producing feelings of pleasure and reward (Saigusa, Aono, & Waddington, 2017). The DA reward system is also regulated by hormones and nutrients.…”
mentioning
confidence: 99%
“…In this sense, μ-opioid receptor (MOR) is an important mediator of rewarding properties and additive behavior [ 69 , 70 ] and they are located in the GABAergic interneurons [ 71 ]. NAc is a brain area with considerable MOR density [ 72 ]. Increased MOR resulting from psychostimulant drug administration is related to increased vulnerability to relapse [ 73 ], what was also observed in our AMPH-exposed animals.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most obvious interaction between the two systems is that MOR activation by exogenously administered agonists, such as morphine, stimulate dopamine release in the NAc. Further, KOR activation reduces dopamine release (Escobar et al, 2020), and DOR activation may increase dopamine release to some extent (Saigusa et al, 2017) or have no effect on dopamine (Longoni et al, 1998).…”
Section: Enkephalinergic Modulation Of Dopamine Neurotransmissionmentioning
confidence: 99%
“…MOR agonists increase dopamine in the dorsal and ventral striatum (via disinhibition) by activating MORs in the VTA/substantia nigra. MORs do not seem to be located presynaptically on dopamine terminals in the NAc (Svingos et al, 1996;Britt and McGehee, 2008;Saigusa et al, 2017; but see Svingos et al, 1999), but may be present presynaptically in the VP to gate dopamine release arising from the VTA (Mitrovic and Napier, 2002;Root et al, 2015;Clark and Bracci, 2018).…”
Section: Enkephalinergic Modulation Of Dopamine Neurotransmissionmentioning
confidence: 99%
See 1 more Smart Citation